Intracranial Hemorrhage After Reperfusion Therapies in Acute Ischemic Stroke Patients - Maïer, Benjamin; Desilles, Jean Philippe; Mazighi, Mikael (Frontiers in Neurology, 2020)
Reperfusion therapies are the mainstay of acute ischemic stroke (AIS) treatments and overall improve functional outcome. Among the established complications of intravenous (IV) tissue-type plasminogen activator (tPA), intracranial hemorrhage (ICH) is by far the most feared and has been extensively described by seminal works over the last two decades. Indeed, IV tPA is associated with increased odds of any ICH and symptomatic ICH responsible for increased mortality rate during the first week after an AIS. Despite these results, IV tPA has been found beneficial in several pioneering randomized trials and improves functional outcome at 3 months. Endovascular therapy (EVT) combined with IV tPA for AIS patients consecutive to an anterior circulation large-vessel occlusion does not increase ICH occurrence. Of note, EVT following IV tPA leads to significantly higher rates of early reperfusion than with IV tPA alone, with no difference in ICH, which challenges the paradigm of reperfusion as a major prognostic factor for ICH complications. However, several blood biomarkers (glycemia, platelet and neutrophil count), clinical factors (age, AIS severity, blood pressure management, diabetes mellitus), and neuroradiological factors (cerebral microbleeds, infarct size) have been identified as risk factors for ICH after reperfusion therapy. In the years to come, the ultimate goal will be to further improve either reperfusion rates and functional outcome, while reducing hemorrhagic complications. To this end, various approaches being investigated are discussed in this review, such as blood-pressure control after reperfusion or the use of new antiplatelet agents as an adjunct to IV tPA and exhibit reduced hemorrhagic potential during the early phase of AIS.